Cyclic Scheduling Problem of a Flexible Robotic Cell with a Self-Buffered Robot - Al-Hindwan, Fatma Mohamed Ali (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Extensive usage of automatic processing in industries has created Flexible Manufacturing Systems (FMSs). In a robotic FMS there are some Computer Numerical Control (CNC) machines for processing the parts, there is an input buffer for keeping unprocessed parts and an output buffer for finished parts, and at least one robot for transporting the parts in the system and loading/unloading the machines, and a central computer controlling the system. Such systems provide advantage in flexibility and standardization in production systems and they have been employed in recent years in order to keep up with the market competition. In order to use the system efficiently the system should be scheduled carefully. In this content, the order of the robot actions such as robot movements and loading/unloading activities should be determined for maximizing the system’s efficiency. When the system repeats a cycle in its run maximizing the efficiency is equivalent to minimizing the cycle time. This thesis considers a robotic FMS in which there is a single self-buffered robot which has the ability to carry more than one part at a time in an inline robotic cell where parts produced are identical. The system repeats a cycle in its long run. The problem is to determine the schedule of the system for minimizing the cycle time. A Mixed Integer Programming (MIP) model of the problem is developed to find the optimal solutions. Since the developed MIP model could not solve the large size problems a Simulated Annealing meta-heuristic algorithm is developed to solve those problems. Performances of the proposed methods and considered robotic FMS cells are evaluated on several numerical instances. Numerically, it has been shown that the performances of the proposed methods are satisfactory and the performance of the robotic FMS increases significantly by using a self-buffered robot up to some robot buffer capacity. After a point more robot buffer capacity becomes useless. Keywords: Flexible Manufacturing Systems, Cyclic Robotic FMS Scheduling, Self-Buffered Robot.

ÖZ: Sanayide otomasyona dayalı üretimin geniş şekilde kullanımı Esnek Üretim Sistemleri’ni (EÜSleri’ni) ortaya çıkarmıştır. Robotlu bir EÜS’de parçaları işlemek için CNC makineler, işlenmemiş parçaları tutmak için bir stok alanı, bitmiş parçalar için bir stok alanı, parçaları sistemde taşımak ve makineleri yüklemek/boşaltmak için en az bir robot ve sistemi kontrol eden bir merkezi bilgisayar vardır. Böyle sistemler esneklik ve standartlaşma konularında avantaj sağlamaktadır ve son yıllarda rekabet edebilmek için tercih edilmektedirler. Sistemin verimli bir şekilde kullanılabilmesi için dikkatlice çizelgelenmesi gerekmektedir. Bu kapsamda, robot hareketi ve yükleme/boşaltma gibi robot faaliyetleri sistem verimliliğini en büyükleyecek şekilde belirlenmelidir. Sistem çalışırken bir döngüyü tekrarlıyor ise döngü süresinin en küçüklenmesi sistem verimliliğinin en büyüklenmesiyle aynıdır. Bu tezde, birden fazla parçayı aynı anda taşıyabilecek kendi stok alanına sahip bir robotun bulunduğu ve parçaların özdeş olduğu bir robotlu EÜS ele alınmıştır. Sistem uzun süreli çalışmasında bir döngüyü tekrarlar. Problem, döngü süresini en küçükleyecek sistem çizelgesinin bulunmasıdır. En iyi çözümleri bulmak üzere problemin Karışık Tamsayılı Programlama (KTP) modeli geliştirilmiştir. Geliştirilen KTP modeli büyük boyutlu problemleri çözemediği için bu problemleri çözmek amacı ile Tavlama Benzetimi modern-sezgisel algoritması geliştirilmiştir. Geliştirilen yöntemlerin ve ele alınan EÜS hücresinin performansları çeşitli sayısal problemler üzerinden değerlendirilmiştir. Önerilen yöntemlerin memnun edici bir performansa sahip oldukları ve ele alınan robotlu EÜS’nin performansının kendi stok alanı olan robot kullanılarak belli bir stok kapasitesine kadar önemli derecede arttığı sayısal olarak gösterilmiştir. Belli bir noktadan sonra daha fazla robot stok alanının olması faydasızdır. Anahtar Kelimeler: Esnek Üretim Sistemleri, Döngülü Robotlu EÜS Çizelgeleme, Kendinden Stok Alanlı Robot.
Master of Science in Industrial Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Industrial Engineering, 2018. Supervisor: Assist. Prof. Dr. Hüseyin Güden.
Keywords: Industrial Engineering; Manufacturing processes--Flexible Manufacturing Systems; Mechanization--factory operations engineering; Computer-aided manufacture; Flexible Manufacturing Systems; Cyclic Robotic FMS Scheduling; Self-Buffered Robot